The Proof of the Collatz Conjecture - Mohammadhoseini, Bahman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In this paper, I intend to prove the Collatz conjecture. In the following, I will prove that the Collatz conjecture is true for any positive integer and also for natural numbers. That is, after sufficiently using the rules of the Collatz conjecture, we must reach 1. In fact, I aim to give a definite answer to the question that has not been answered since 1937: Does the Collatz sequence eventually reach 1 for all-natural or positive integer initial values? My answer is yes.